Lie. stragùs = sl. *strogъ - Karaliūnas, Simas (Baltistica, 1968)
LITH. stragùs = SL. *strogъLith. stragùs/stregùs “severe, stern, cruel, strong, vigorous, angry, obstinate…” is an old Baltic word the equivalents of which in other IE languages seem to be Common Slavic *strogъ “severe, cruel, strong…” (Russian, Ukrainian строгий Belorussian строгi, Polish strogi, Czech, Slovak strohý etc.) and Middle High German strac (strack) “tight, taut, direct”, Middle Low German strak (strack) “stiff, fixed, firm, raised; stubborn, headstrong” and Anglo-Saxon strec “stiff, numb, severe, rigorous, stern, strong”. All these words probably belong to the IE root *(s)treg- “harden, become hard; hard, stiff…” the immediate continuants of which are attested in the East Baltic languages, cf. Lith. strė́gti “harden, congeal, freeze”, Latvian streģele, strēģele “icicle“ etc. The change of meaning from “harden, become hard; hard, stiff…” to “severe, cruel, strong, rigorous, angry, obstinate…” can easily be explained (cf. Lat. rigidus “hard, stiff… rude, cruel, violent” and Lat. frīgus, -oris „frost; shudder, shiver”, Gr. ργος „frost; shudder, shiver”; Gr. στερεός „hard, stiff, firm; obstinate; cruel” and Lith. star-ìnti „to make hard, stiff; stretch…” etc).Inspite of the fact that Latvian strieģele „icicle“ has the same meaning as Latvian streģele, strēģele, it probably belongs to quite a different root and may be identified with Lat. frīgus, -oris „frost; shudder, shiver” and Gr. ῥῖγος “frost; shudder, shiver” (< IE *srīgos-).Polish srogi “cruel, severe, violent…”, Middle Bulgarian sragь “terrible, frightful, dreadful”, Russian Church Slavonic срагъ “terrible, dreadful”, Old Church Slavonic sraga “disease“, Russian сорога “a gloomy, difficult man” must in all probability be distinguished from the two groups of words mentioned above and identified with Lith. sir̃gti “to be ill”, sargìnti, sárgalioti „to be ailing, to be sickly” and Latvian sìrgt “to be ill”, sȩ̀rga „ilness, disease”, sȩ̄rgalât “to be ailing”.
Keywords: lietuvių; stragus; etimologija